ANALISIS OMSET DAN POSISI BERSAING PADA KLASTER USAHA KECIL MENENGAH (UKM) SEPATU KOTA MOJOKERTO - Fitanto, Bahtiar (Journal of Indonesian Applied Economics, 2009)
This articles describes about turnover and competitiveness position of footwear smalland medium scale enterprises (sme’s) at Mojokerto, East Java Province. SME’s clus-ter approach is used to get the full maps of the ptroblem and policies that are needed.Development of small and medium scale enterprises is plays a crucial role for localeconomic development. This article is important because there are thousands of foot-wear small and medium scale enterprises in Mojokerto.Keywords: small and medium scale enterprises, local economic development, clus-ter